2024
DOI: 10.1029/2023gb007953
|View full text |Cite
|
Sign up to set email alerts
|

The Net GHG Balance and Budget of the Permafrost Region (2000–2020) From Ecosystem Flux Upscaling

Justine Ramage,
McKenzie Kuhn,
Anna‐Maria Virkkala
et al.

Abstract: The northern permafrost region has been projected to shift from a net sink to a net source of carbon under global warming. However, estimates of the contemporary net greenhouse gas (GHG) balance and budgets of the permafrost region remain highly uncertain. Here, we construct the first comprehensive bottom‐up budgets of CO2, CH4, and N2O across the terrestrial permafrost region using databases of more than 1000 in situ flux measurements and a land cover‐based ecosystem flux upscaling approach for the period 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 155 publications
0
3
0
Order By: Relevance
“…Furthermore, changes in soil carbon dynamics can influence climate-carbon feedback loops, with the potential to exacerbate the rate and magnitude of climate change (Heimann & Reichstein, 2008;Paustian et al, 2016). For example, the thawing of permafrost soils in high-latitude regions can release large amounts of greenhouse gasses, including methane (CH 4 ), nitrous oxide (N 2 O), and carbon dioxide (CO 2 ) into the atmosphere, further accelerating global warming and permafrost degradation (Gasser et al, 2018;Ramage et al, 2024;Schuur et al, 2015;Voigt et al, 2020). Similarly, the loss of soil carbon, nutrients, and fertility in tropical forests due to deforestation and land degradation can reduce the resilience of these ecosystems to climate change and increase the risk of significant ecosystem change (Dlamini et al, 2014;Labrière et al, 2015;Mitchard, 2018;Veldkamp et al, 2020).…”
Section: The Role Of Soils For Climate Regulationmentioning
confidence: 99%
“…Furthermore, changes in soil carbon dynamics can influence climate-carbon feedback loops, with the potential to exacerbate the rate and magnitude of climate change (Heimann & Reichstein, 2008;Paustian et al, 2016). For example, the thawing of permafrost soils in high-latitude regions can release large amounts of greenhouse gasses, including methane (CH 4 ), nitrous oxide (N 2 O), and carbon dioxide (CO 2 ) into the atmosphere, further accelerating global warming and permafrost degradation (Gasser et al, 2018;Ramage et al, 2024;Schuur et al, 2015;Voigt et al, 2020). Similarly, the loss of soil carbon, nutrients, and fertility in tropical forests due to deforestation and land degradation can reduce the resilience of these ecosystems to climate change and increase the risk of significant ecosystem change (Dlamini et al, 2014;Labrière et al, 2015;Mitchard, 2018;Veldkamp et al, 2020).…”
Section: The Role Of Soils For Climate Regulationmentioning
confidence: 99%
“…The current C balance of Arctic tundra is uncertain, with contrasting signs reported in literature (Commane et al, 2017;Euskirchen et al, 2017;McGuire et al, 2012;Ramage et al, 2024;Virkkala et al, 2021). For the Toolik Lake area, tundra ecosystems are sources of CO 2 due to strong emissions during non-growing seasons (Commane et al, 2017;Euskirchen et al, 2017), and the C loss is thought to accelerate in the future primarily owing to the positive feedback from permafrost thaw that further increases ecosystem respiration (Hugelius et al, 2020;Schuur et al, 2009;Turetsky et al, 2020).…”
Section: Carbon-cycle Implications and Future Prioritiesmentioning
confidence: 99%
“…However, the response of tundra ecosystems to future climate change and the fate of their large soil C stocks are unclear, in particular for belowground processes and associated C budgets (Bouskill et al, 2020;Sistla et al, 2013). Using different methods and data sets, previous studies of ecosystem C fluxes have suggested that Arctic tundra ecosystems likely function as CO 2 sources, sinks, or are almost CO 2 -neutral at present (Commane et al, 2017;Euskirchen et al, 2017;McGuire et al, 2012;Ramage et al, 2024;Virkkala et al, 2021). Earth system models also have limited skills in representing modern C stocks and fluxes of Arctic tundra (Commane et al, 2017;Todd-Brown et al, 2013) and are highly uncertain in predicting their future changes in C cycling (Natali et al, 2019;Qian et al, 2010;Tao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%